Практика копірайтингу та візуалізації у екологічному і етичному маркетингу - Ткачук (Стахурська), Світлана Валеріївна; Стахурський, Валерій Олександрович (My University, 2022)
У статті розглядаються практичні підходи та приклади маркетингових комунікацій в аспекті екологічного й етичного маркетингу. Екологічний маркетинг розглядається як впровадження принципів «еко-френдлі» у маркетингову та виробничу політику підприємства, включаючи натуральність, корисність товарів, екологічність виробництва, упаковки, акцент на екологічності пропозиції у рекламних кампаніях. Етичний маркетинг – досить широке поняття, втім у даній статті розглядається аспект «Круелті-фрі», тобто етичне ставлення до живих істот на всіх етапах виробництва та реалізації продукції: недопущення вівісекції, забезпечення належних умов утримання тварин у відповідності до їх потреб, вільний вигул тощо. Маркетингові комунікації в аспекті екологічної й етичної відповідальності пропонується поділяти на дві групи: комерційні та некомерційні. Некомерційні комунікації (соціальна реклама) створюють базу для попиту на товари «еко-френдлі» та «круелті-фрі», тоді як комерційні маркетингові комунікації допомагають фірмі-виробнику чи ритейлеру позиціонувати себе як екологічно-відповідального суб’єкта господарювання, підкреслювати відповідну цінність своєї пропозиції, а також сприяти усвідомленню людиною екологічних цінностей як сучасного тренду. Комерційні і некомерційні комунікації разом допомагають досягти таких цілей як формування правильних потреб, екологічної відповідальності та раціонального споживання, а також стимулювання попиту на відповідні товари. У обох видах комунікацій значна роль належить копірайтингу та візуальним ефектам. Правильно підібрана сукупність вербальних та невербальних компонентів, розуміння психології сприйняття кольорів, шрифтів та прийомів композиції допомагає краще донести комунікативне повідомлення до цільової аудиторії, сформувати правильні цінності та підкреслити відповідне позиціонування фірм-виробників. The article considers practical approaches and examples of marketing communications in the aspect of ecological and ethical marketing. Environmental marketing is considered as the implementation of the principles of "eco-friendly" in the marketing and production policy of the enterprise, including naturalness, usefulness of goods, environmental friendliness of production, ecological packaging and emphasis on environmental friendliness in advertising campaigns. Ethical marketing is a fairly broad concept, but this article discusses the aspect of "Cruelty-free", such as ethical treatment of living beings at all stages of production and sale: prevention of vivisection, ensuring proper conditions for keeping animals in accordance with their needs, free walking, etc. It is proposed to divide marketing communications in the aspect of ecological and ethical responsibility into two groups: commercial and non-commercial. Non-commercial communications (social advertising) create a basis for demand for "eco-friendly" and "cruelty-free" goods, while commercial marketing communications help the manufacturer or retailer to position itself as an environmentally responsible business entity, emphasize the value of its proposals, as well as to promote human awareness of environmental values as a modern trend. Commercial and non-commercial communications together help to achieve such goals as the formation of the right needs, environmental responsibility and rational consumption, as well as stimulating demand for relevant goods. Copywriting and visual effects play a significant role in both types of communications. Practical examples of the use of verbal and nonverbal techniques in commercial marketing communications and social advertising are analyzed. In particular, the methods of copywriting and visualization were studied on the example of the brand block of the Vega-Market store, the MotherFarm eco-farm, some methods of advertising text of the official MotherFarm website, as well as communication components of one of MotherFarm's products. Visual and textual effects of social environmental advertising posted on the social network page of the EcoVida Imbituba store are analyzed. Properly selected set of verbal and nonverbal components, understanding the psychology of color perception, fonts and techniques of composition helps to better convey the communicative message to the target audience, form the right values and emphasize the appropriate positioning of manufacturers.
Keywords: екологічний маркетинг; етичний маркетинг; еко-френдлі; круелті-фрі; копірайтинг; візуалізація; маркетингові комунікації; ecological marketing; ethical marketing; eco-friendly; cruelty-free; copywriting; visualization; marketing communications; кафедра маркетингу